A New Method to Enhance the Light–Matter Interaction by Controlling the Resonance of Electrons - Xuefang Hu; Haoyang Mao; Sisi Yang; Changgui Lu; Xiangyue Zhao; Mengjia Lu (Photonics)
The manipulation of surface plasmon polaritons (SPPs) plays an essential role in plasmonic science and technology. However, the modulation efficiency and size of the device in the traditional method suffer from weak light–matter interaction. Herein, we propose a new method to enhance the light–matter interaction by controlling the resonance of electrons in a sandwich structure which is composed of an interdigital electrode, dielectric, and doped semiconductor. The numerical results show that the resonance of electrons occurs when their vibrational frequency under electrostatic field matches well with the oscillation frequency of the propagating SPPs. The intensity of the electric field is enhanced about 8%, which can be utilized to improve the modulation efficiency and minimize the footprint of device to a great extent. These findings pave a new way towards higher precision sensor and more compact modulator.